Transversal Kerr effect enhancement of permalloy-based shallow lamellar magnetoplasmonic crystals - Murzin, Dmitry; Belyaev, Victor; Kern, Johannes; Kaspar, Corinna; Pernice, Wolfram; Bratschitsch, Rudolf; Rodionova, Valeria (Photonics, 2022)
This work demonstrates spectral dependencies of reflectivity and the transversal Kerr effect of a series of permalloy magnetoplasmonic crystals based on shallow lamellar diffraction gratings with a period of 500 nm, stripe’s width of 250 nm, and diffraction stripes’ heights of 28, 43, 67, and 88 nm. The fabricated magnetoplasmonic crystals show a monotonic increase of the transversal Kerr effect and the diffraction figure-of-merit with higher diffraction stripes. The maximum achieved modulation value of the transversal Kerr effect was found to be 0.78%, which can be further tuned by the periodicity and stripes width of the magnetoplasmonic crystals.